2023
DOI: 10.1177/03635465231162644
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effects of Triamcinolone and Methylprednisolone on the Viability and Mechanics of Native Articular Cartilage

Nathan P. Fackler,
Evelia Yareli-Salinas,
Kylie T. Callan
et al.

Abstract: Background: The chondrotoxic effects of methylprednisolone acetate (MP) and triamcinolone acetonide (TA) have been well described. However, the mechanical effects of these commonly used steroids on native cartilage are largely unknown. Purpose: To investigate the in vitro effects of a single 1-hour MP or TA exposure on the viability, mechanics, and biochemical content of native articular cartilage explants. Study Design: Controlled laboratory study. Methods: Articular cartilage explants (n = 6 per group) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Severe in vitro toxicity of betamethasone and methylprednisolone has been reported in canine‐explanted chondrocytes and synoviocytes [ 59 ]. Multiple studies suggested the detrimental effect of CS on human chondrocyte viability in vitro, with both triamcinolone and methylprednisolone showing chondrotoxic effects, and dexamethasone and even more betamethasone presenting a dose‐dependent effect on cellular necrosis [ 19 , 20 , 22 , 23 , 61 ]. Overall, the in vitro studies warn against the possible detrimental effects of CS and underline the importance of investigating molecules and doses with the best risk/benefit ratio to treat OA joints.…”
Section: Discussionmentioning
confidence: 99%
“…Severe in vitro toxicity of betamethasone and methylprednisolone has been reported in canine‐explanted chondrocytes and synoviocytes [ 59 ]. Multiple studies suggested the detrimental effect of CS on human chondrocyte viability in vitro, with both triamcinolone and methylprednisolone showing chondrotoxic effects, and dexamethasone and even more betamethasone presenting a dose‐dependent effect on cellular necrosis [ 19 , 20 , 22 , 23 , 61 ]. Overall, the in vitro studies warn against the possible detrimental effects of CS and underline the importance of investigating molecules and doses with the best risk/benefit ratio to treat OA joints.…”
Section: Discussionmentioning
confidence: 99%